Representasi Bulliying pada Film MUNKAR - Tantri, Herlina; Siswati, Endah; Harumike, Yefi Dyan Nofa (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2024)
Anxiety about everyday events, such as violence and intimidation. One form of social violence that is often the focus of horror films is Bulliying. Bulliying is deliberate threats or actions to physically, verbally or mentally dominate, hurt or eliminate someone, carried out repeatedly to make a vulnerable victim feel intimidated and threatened. One of the horror films that represents the phenomenon of Bulliying is "Munkar". Therefore, researchers conducted research with the aim of finding out how Bulliying is represented in the horror film "Munkar" by analyzing scenes that show forms of Bulliying using Roland Barthes' semiotic analysis.